VISION: A Regional Performance Improvement Initiative for HIV Health Care Providers. Issue 3 (June 2014) - Bruno, Theodore O.; Hicks, Charles B.; Naggie, Susanna; Wohl, David A.; Albrecht, Helmut; Thielman, Nathan M.; Rabin, Daniel U.; Layton, Sherry; Subramaniam, Chitra; Grichnik, Katherine P.; Shlien, Amanda; Weyer, Dianne
<x xml:space="preserve">Abstract</x> Introduction VISION (HIV Integrated Learning ModuleS: Achieving Performance Improvement through CollaboratiON) was a regional performance improvement (PI) continuing medical education (CME) initiative designed to increase guideline‐conforming practice of clinicians who manage patients with HIV infection. Methods The 3‐part activity consisted of (1) clinical practice assessment and development of an action plan for practice change, (2) completion of relevant education, and (3) reassessment. Results The activity did not change practitioners' performance in clinical status monitoring and in patient treatment, in large part because guidelines were being appropriately implemented at baseline as well as after the educational intervention. There was a trend toward improvement, however, in practitioner performance in the area of patient medication adherence (increased from 66% to 74%). Discussion Results observed in the VISION initiative were consistent with HIVQUAL metrics. Ongoing education in HIV is important, and VISION demonstrated performance improvement in medication adherence, a critical aspect of health care.